Code-switching and Code-mixing on Deddy Corbuzier’s Podcast Youtube Channel: October 5, 2022 - Hadi Saputra (ELITE Association Indonesia, 2023)
Recently, podcast content on social media Youtube has been very popular and received well by the public. One of them is Deddy Corbuzier's podcast 'Close the Door' which is the object of research in this study. Object retrieval is based on the speech by Deddy Corbuzier and his guest, Reza Arap. Throughout the video, they use Indonesian and a foreign language, namely English, interchangeably. In addition, both of them also insert English word elements. This study is descriptive qualitative research and is aimed to determine: (1) The types of code-switching in Deddy Corbuzier's video podcast; (2) The types and forms of code-mixing in Deddy Corbuzier's video podcast; (3) The causal factors of occurrence of code-switching and code-mixing. The analysis results of this study indicate that there are external code-switching types from Indonesian to English speech and vice versa. There are also outer code-mixing types and forms and code-mixing forms with the insertion of English elements in the form of nouns, adjectives, verbs, adverbials, and phrases. The causal factors of code-switching events are speakers, interlocutors, and changes in conversation topics. While the factors that cause code-mixing events are prestige motives and urgent needs. keywords: campur kode, faktor penyebab.